2017
DOI: 10.1126/scitranslmed.aam8012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of population viral load on prospective HIV incidence in a hyperendemic rural African community

Abstract: Monitoring HIV population viral load (PVL) has been advocated as an important means of inferring HIV transmission potential and predicting the future rate of new HIV infections in a particular community. However, the relationship between the PVL measures and directlymeasured HIV incidence has not been quantified in any setting and most importantly not in a hyper-endemic sub-Saharan African setting. We assessed this relationship using one of Africa's largest population-based prospective population cohorts, in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
84
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 33 publications
10
84
0
1
Order By: Relevance
“…Although earlier multi‐city studies in other countries emphasized the influence of HIV seroprevalence on HIV incidence rates among PWID, more recent studies suggest that community viral suppression, regardless of HIV seroprevalence rate, is a stronger predictor of HIV incidence in high‐risk populations . In this study and previous studies, we show better awareness of HIV status and greater community viral suppression among PWID in the Northeast compared to those in the North/Central region .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although earlier multi‐city studies in other countries emphasized the influence of HIV seroprevalence on HIV incidence rates among PWID, more recent studies suggest that community viral suppression, regardless of HIV seroprevalence rate, is a stronger predictor of HIV incidence in high‐risk populations . In this study and previous studies, we show better awareness of HIV status and greater community viral suppression among PWID in the Northeast compared to those in the North/Central region .…”
Section: Discussionsupporting
confidence: 49%
“…Although the response to injection drug use in India has historically been punitive, the benefits of shifting towards a harm reduction approach is highlighted by the experience of the Northeastern states which were the first to institute widespread HIV prevention and treatment efforts based on harm reduction principles. Although earlier multi-city studies in other countries [59] emphasized the influence of HIV seroprevalence on HIV incidence rates among PWID, more recent studies suggest that community viral suppression, regardless of HIV seroprevalence rate, is a stronger predictor of HIV incidence in high-risk populations [60,61]. In this study and previous studies, we show better awareness of HIV status and greater community viral suppression among PWID in the Northeast compared to those in the North/Central region [19,62].…”
Section: Discussionmentioning
confidence: 95%
“…Tanser et al ., using data from another rural community in KwaZulu‐Natal, found that HIV incidence was not directly associated with PVS but rather with population viral load metrics that account for HIV prevalence . As HIV prevalence remained almost stable during the trial, we cannot exclude the possibility that HIV incidence may have been decreasing in both arms.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the PLHIV population turnover in the trial area was high, more than one fifth being replaced every year, mainly due to out-and in-migration as well as the continuous inflow of new HIV infections, attenuating the impact of the interventions on the cascade of HIV care and subsequently the differences between arms [26]. Tanser et al, using data from another rural community in KwaZulu-Natal, found that HIV incidence was not directly associated with PVS but rather with population viral load metrics that account for HIV prevalence [27]. As HIV prevalence remained almost stable during the trial, we cannot exclude the possibility that HIV incidence may have been decreasing in both arms.…”
Section: Discussionmentioning
confidence: 99%
“…ART has dramatically improved survival for people living with HIV (PLHIV) and globally there has been an improvement in treatment coverage . Viral suppression on ART confers an individual health benefit , and a significant reduction in the risk of onward transmission , with an impact on HIV incidence at a population level . In 2014, the Joint United Nations Programme on HIV and AIDS (UNAIDS) set the 90‐90‐90 targets, whereby 90% of people with HIV will know their status, 90% diagnosed will be on ART and 90% on ART will be virally supressed by 2020 .…”
Section: Introductionmentioning
confidence: 99%